New Perspectives for Curricular Development of Dual Education (Global Journal of Human-Social Science, 2025)
Curricular development has always been a widely discussed issue in society Considering the specifics of technical vocational education curricular development is carried out only in partnership with the private sector When representatives of the private sector lack sufficient resources to engage in curricular development the educational environment is unable to create vocational training offerings that align with the trends of market economy development In this article we aim to address the subject of curricular development from the perspective of dual education which takes place through close cooperation between educational institutions and representatives of the private sector The article covers topics such as the fundamental principles of curricular development in dual education the structure of the vocational training process Curriculum Plan for dual education the benefits of dual education for students economic units educational institutions and the state We believe that the topic addressed will be of interest to both the educational and private sectors at both national and international levels
Keywords: apprenticeship; curriculum; economic entities; education; labor market needs; technical professional education